Branding Strategy Analysis at Ngudi Waluyo University - Septiana, Hafida Eka; Prihatin, Titi; Hudallah, Noor; Oktarina, Nina (Educational Management, 2022)
This study focuses on the importance of branding strategies in the education sector, with specific emphasis on Ngudi Waluyo University (UNW), a new private university in Semarang Regency. The objective of the research was to analyze and identify brand positioning strategies, brand identity strategies, brand personality strategies, and brand communication strategies employed by UNW. A qualitative approach was employed, utilizing interviews, observation, and documentation as sources of direct, descriptive data. UNW's brand positioning strategy is built upon its vision and mission. The brand identity strategy centers around the symbol of UNW, which signifies sincerity, neutrality, and a cultured attitude in the university's contribution to national education, aiming for a glorious Indonesia. The brand personality strategy involves collaboration with competent stakeholders. UNW's brand communication strategy encompasses the establishment of Memorandums of Understanding (MoUs) with various agencies, particularly schools in Central Java and Tri Dharma, as well as practice areas and government institutions such as the Ministry of Law and Human Rights of Central Java and the Government of Timor Leste. These MoUs also incorporate the KOKY program. To enhance its branding, UNW is advised to strengthen its position through innovative initiatives. By consistently improving the quality of education, UNW can establish a strong brand image and increase its competitive advantage in the education sector.